An den Grenzen Europas und des Rechts: Interdisziplinäre Perspektiven auf Migration, Grenzen und Recht - Tohidipur, Timo; Pichl, Maximilian (transcript, 2019)
This volume examines the conditions of people's access to Europe and the relevance of law and borders in interdisciplinary perspectives.